1919 Colo. Sess. Laws 416-17 - (:unkn) unknown (My University, 1919)
Foreign-Born Unnaturalized Citizens, § 1: Prohibited noncitizens from owning or possessing any shotgun, rifle, pistol or firearm of any kind; violators subject to fine, imprisonment, confiscation of weapon.
Keywords: POSSESSION - DANGEROUS PERSONS